Former Yugoslav Republic of Macedonia : 2015 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that the economic recovery of Former Yugoslav Republic of Macedonia has strengthened. Real GDP growth accelerated to 3.8 percent in 2014, from 2.7 percent in 2013. Strong growth was attributed to double-digit growth in investment driven by activities in the Technological Industrial Development Zones and public infrastructure, as well as strong private consumption supported by robust credit growth and improving labor market conditions. GDP growth in 2015 is expected to moderate to 3.2 percent, with significant downside risks. A derailment of recent political agreement could negatively impact economic sentiment and growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet